Bromodomain factors of BET family are new essential actors of pericentric heterochromatin transcriptional activation in response to heat shock - Edwige Col (Nature Portfolio, 2017)
Abstract The heat shock response is characterized by the transcriptional activation of both hsp genes and noncoding and repeated satellite III DNA sequences located at pericentric heterochromatin. Both events are under the control of Heat Shock Factor I (HSF1). Here we show that under heat shock, HSF1 recruits major cellular acetyltransferases, GCN5, TIP60 and p300 to pericentric heterochromatin leading to a targeted hyperacetylation of pericentric chromatin. Redistribution of histone acetylation toward pericentric region in turn directs the recruitment of Bromodomain and Extra-Terminal (BET) proteins BRD2, BRD3, BRD4, which are required for satellite III transcription by RNAP II. Altogether we uncover here a critical role for HSF1 in stressed cells relying on the restricted use of histone acetylation signaling over pericentric heterochromatin (HC).